Translating the Sacred: The Role of Expansion in Mediating Cultural and Sensitive Elements in English and Malay Qur’anic Translations - Sulhah Ramli; Hishomudin Ahmad; Norzulaili Mohd Ghazali; Robiatul Adawiyah Mohd @ Amat (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia